Sex Work and the New Zealand Model : Decriminalisation and Social Change - Abel, Gillian; Abel, Gillian; Armstrong, Lynzi; Armstrong, Lynzi (Book collections on Project MUSE., 2020)
More than 15 years have passed since the law regarding sex workers in New Zealand has changed. As a model it has been endorsed as best practice by international organisations, leading scholars and sex worker-led organisations. Yet in some corners, speculation is ongoing regarding its impacts on the ground. Written by an international group of experts, this groundbreaking collection provides the much needed in-depth research into how decriminalisation is playing out in sex workers' lives and how different groups of sex workers are experiencing it, while uncovering the challenges and tensions that remain to be negotiated in this field. Using the evidence from New Zealand, it makes an invaluable contribution to the international debates regarding sex work laws and the global struggle to realise sex workers' rights.